2016
DOI: 10.1108/wwop-02-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Computer classes for older people: motivations and outcomes

Abstract: Computer classes for older people: motivations and outcomes. ABSTRACTPurpose: A 'digital divide' exists between older and younger people in terms of computer use and older people's uptake of computer training programmes in the UK remains low. This study aims to identify the motivations and outcomes of computer classes for some older people and the contributory factors.Design/methodology/approach: One-to-one qualitative semi-structured interviews were conducted with eight participants at a computer class in a L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The social advantages of group learning are notable. Group settings encourage peer learning and support, enhance social inclusion (Wlodkowski, 1999), and increase confidence (Zaidman and Tinker, 2016). Vygotsky (1978) suggested that whilst individual learning could increase knowledge and skills, collaboration with more informed peers could further enhance this and expand the zone of proximal development, the distance between current developmental stage and maximum potential development.…”
Section: Discussionmentioning
confidence: 99%
“…The social advantages of group learning are notable. Group settings encourage peer learning and support, enhance social inclusion (Wlodkowski, 1999), and increase confidence (Zaidman and Tinker, 2016). Vygotsky (1978) suggested that whilst individual learning could increase knowledge and skills, collaboration with more informed peers could further enhance this and expand the zone of proximal development, the distance between current developmental stage and maximum potential development.…”
Section: Discussionmentioning
confidence: 99%
“…Facilitating a smooth transition back into the classroom, after what may have been an extended absence, can help ensure the learning environment feels like an empowering and welcoming space ( Baringer et al, 2004 ). It would also be prudent to consider the social aspect of these digital skills programs as providing learners the opportunity to meet new people through these classes may increase engagement with the class and increase confidence ( Good Things Foundation and Talk Talk, 2018 ; ( Zaidman & Tinker, 2016 ). Therefore, teaching older adults provides an opportunity to collaborate with the learners, and create a sense of social inclusion ( R.J Wlodkowski, 2008 ).…”
Section: Discussionmentioning
confidence: 99%